Utilization of groundwater treatment sludge and sludge-derived manganese dioxide for the removal of nickel ions from aqueous solutions - Ong, Dennis C.
Groundwater treatment sludge contains manganese components that are unutilized and disposed along with the rest of the solid waste. In this study, the potential of groundwater treatment sludge reuse in the adsorption of nickel ions from aqueous solutions was evaluated. Results showed that the pH level had no significant effect on the Ni(II) removal. The nickel adsorption on the sludge at all pH levels was described by the Freundlich model, with adsorption affinity constant (n value) implying chemical adsorption. The kinetic data of nickel adsorption on the sludge at pH 6.5 and initial Ni(II) concentrations of 50, 100 and 200 mg L-1 was best described by the pseudo-second order adsorption kinetic rate model, indicating that chemisorption between the sludge binding sites and Ni(II) governs the adsorption process. The results confirm the applicability of the groundwater treatment sludge as a low-cost alternative for nickel removal from wastewater. Recovery of manganese from groundwater treatment sludge through reductive leaching was also investigated. Maximum leached Mn (100 percent) was obtained using H2SO4 and H202 at 25 degree celsius. At this temperature, the rate-limiting step of Mn leaching was diffusion through inert solid components of the sludge, composed mainly of the insoluble sand particles. Maximum precipitation of Fe and separation from Mn in the leachate through addition of KOH occurred at pH 4.0. The results demonstrated that reductive leaching and precipitation process is an effective means of recovering Mn from the groundwater treatment sludge. Application of the recovered manganese in nickel removal from aqueous solution was also explored. Nickel (Ni(II)) adsorption on the synthetic manganese dioxide was best described by the Langmuir isotherm model, as reflected in the high correlation coefficient (Ro) values of 0.9703 to 0.9847. The separation factor (RL) for the pH range and initial Ni(II) concentrations considered implied that the adsorption on the synthetic manganese dioxide was favorable. The kinetic data of nickel adsorption on the synthetic manganese dioxide at pH 6.5 and initial Ni(II) concentrations of 10, 50, 100 and 200 mg L-1 was best described by the pseudo second order adsorption kinetic rate model, with R' values ranging from 0.9997 to 0.9999, indicating that chemisorption occurred through complexation of the Ni(II) ions with the available functional groups on the MnO2. Thermodynamic studies at 298.15, 308.15 and 318.15 K revealed that adsorption was spontaneous and thermodynamically favorable for the 50, 100 and 200 mg L-1 initial Ni(II) concentrations. The adsorption process at all conditions was endothermic, as indicated by the H degree values. MnO2 had good affinity towards the Ni(II) ions, as suggested by the positive ASo at all Ni(II) concentrations.